Policy-driven monitoring and evaluation: Does it support adaptive mana gement of socio-ecological systems? - Waylen, Kerry A.; Blackstock, Kirsty L.; Hulst, Freddy J.; Damian, Carmen; Horváth, Ferenc; Johnson, Richard K.; Kanka, Robert; Külvik, Mart; Macleod, Christopher J. A.; Meissner, Kristian; Oprina-Pavelescu, Mihaela M.; Pino, Joan; et al. (Science of The Total Environment, 2019)
Inadequate Monitoring and Evaluation (M&E) is often thought to hinder adaptive management of socio-ecological systems. A key influence on en vironmental management practices are environmental policies: however, their consequences for M&E practices have not been well-examined. We e xamine three policy areas - the Water Framework Directive, the Natura 2000 Directives, and the Agri-Environment Schemes of the Common Agricu ltural Policy - whose statutory requirements influence how the environ ment is managed and monitored across Europe. We use a comparative appr oach to examine what is monitored, how monitoring is carried out, and how results are used to update management, based on publicly available documentation across nine regional and national cases. The requiremen ts and guidelines of these policies have provided significant impetus for monitoring: however, we find this policy-driven M&E usually does n ot match the ideals of what is needed to inform adaptive management. T here is a tendency to focus on understanding state and trends rather t han tracking the effect of interventions; a focus on specific biotic a nd abiotic indicators at the expense of understanding system functions and processes, especially social components; and limited attention to how context affects systems, though this is sometimes considered via secondary data. The resulting data are sometimes publicly-accessible, but it is rarely clear if and how these influence decisions at any lev el, whether this be in the original policy itself or at the level of m easures such as site management plans. Adjustments to policy-driven M& E could better enable learning for adaptive management, by reconsideri ng what supports a balanced understanding of socio-ecological systems and decision-making. Useful strategies include making more use of seco ndary data, and more transparency in data-sharing and decision-making. Several countries and policy areas already offer useful examples. Suc h changes are essential given the influence of policy, and the urgency of enabling adaptive management to safeguard socio-ecological systems .
Keywords: Adaptive Management; Environmental governance; Monitoring and Evaluation; Policy making; Socio-ecological systems; Sustainability